what is 3(t−3)=5(2t+1)?
Answers
Answered by
4
Solution:-
3(t-3)= 5(2t+1)
⟹3t-9= 10t+5
⟹3t-10t= 5+9
⟹-7t= 14
⟹t= -2
Verification:-
Putting the value of t= -2, we get:-
L.H.S= 3(t-3)= 3(-2-3)= 3(-5)=-15
R.H.S= 5(2t+1)= 5{2×(-2)+1}= 5(-4+1)= 5(-3)= -15
Answered by
0
Answer:
Step-by-step explanation:
brainliest brainliest brainliest brainliest brainliest brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d69/aa364f98777bd9590ee74967a6f56d73.jpg)
Similar questions
World Languages,
7 months ago
Math,
7 months ago
Hindi,
7 months ago
Math,
1 year ago
Physics,
1 year ago